Bioinspired Designs, Molecular Premise and Tools for Evaluating the Ecological Importance of Antimicrobial Peptides - Elvis Legala Ongey; Stephan Pflugmacher; Peter Neubauer (MDPI AG, 2018)
This review article provides an overview of recent developments in antimicrobial peptides (AMPs), summarizing structural diversity, potential new applications, activity targets and microbial killing responses in general. The use of artificial and natural AMPs as templates for rational design of peptidomimetics are also discussed and some strategies are put forward to curtail cytotoxic effects against eukaryotic cells. Considering the heat-resistant nature, chemical and proteolytic stability of AMPs, we attempt to summarize their molecular targets, examine how these macromolecules may contribute to potential environmental risks vis-à-vis the activities of the peptides. We further point out the evolutional characteristics of the macromolecules and indicate how they can be useful in designing target-specific peptides. Methods are suggested that may help to assess toxic mechanisms of AMPs and possible solutions are discussed to promote the development and application of AMPs in medicine. Even if there is wide exposure to the environment like in the hospital settings, AMPs may instead contribute to prevent healthcare-associated infections so long as ecotoxicological aspects are considered.